ANALYSIS OF FACTORS AFFECTING LABOR EFFICIENCY IN INDUSTRIAL ENTERPRISES AND THEIR INDICATORS - Jаmshid Shаrаfetdinоvich Tukhtаbаev,; Nozima Isomiddinovna Soatalieva, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article theoretical are analyzed the essence and a method of definition parameters of efficiency of labour